فعّال وسائل الإعلام الصورة لتطوير مهارة الكلام - Ahmad Mizan Rosyadi Abdul Jalil Manan (INAIFAS PRESS, 2019)
The education system is the real basis for achieving the desired goals in the learning and teaching process, which determines the success of the failure of any educational project. It consists of four important elements, inputs and processes, then outputs or final results, and a comparison of the results obtained with the criteria or objectives set in the feedback. The problems of this research are: How the system of teaching Arabic language to develop speech in terms of inputs, operations or activities, outputs, as well as in terms of feedback. In this research, the researcher chose the descriptive approach with qualitative input. The results of the analysis obtained by the researcher, as follows: that the pictures can make them easily in Arabic speaking than another ways.